2022
DOI: 10.5005/ijcdas-53-2-117
|View full text |Cite
|
Sign up to set email alerts
|

Rare Presentation of Spontaneous Acquired Diaphragmatic Hernia

Abstract: Spontaneous acquired diaphragmatic hernia without any apparent history of trauma is a very rare condition and is very difficult to diagnose. We present a case of a 21-year-old male who presented with abdominal pain for one month and four episodes of vomiting for one day. Clinical suspicion, chest radiography with nasogastric tube in situ and computed tomography (CT) confirmed the diagnosis. The diaphragmatic defect was repaired surgically. The patient had an uneventful post-operative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Acquired diaphragmatic hernias comprise less than 50% of diaphragmatic injuries and are mostly traumatic [7]. Patients often give history of a blunt trauma or road traffic accident [8] and remain undiagnosed in up to 33% cases during the immediate post-traumatic period [9].…”
Section: Discussionmentioning
confidence: 99%
“…Acquired diaphragmatic hernias comprise less than 50% of diaphragmatic injuries and are mostly traumatic [7]. Patients often give history of a blunt trauma or road traffic accident [8] and remain undiagnosed in up to 33% cases during the immediate post-traumatic period [9].…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to reduce the contents back into the abdominal cavity and repairing the defect in the diaphragm. Minimal invasive surgery in the form of laparoscopy or thoracoscopy offers us all the benefits in terms of lesser pain, shorter hospitalization, reduced respiratory complications, and early return to work [3,9]. Although data from randomized control trials is lacking results of both thoracoscopy or laparoscopy have been found to be comparable [9].…”
Section: Acute Phase (Time Between the Originalmentioning
confidence: 99%
“…Acquired DH is most commonly traumatic in origin, mainly due to penetrating or blunt trauma to the abdomen or thorax. Spontaneous DH is a rarity where the patient denies any history of trauma or symptoms and accounts for less than 1% of cases [3,4]. But a possibility of a previously forgotten trauma cannot be ruled out completely.…”
Section: Introductionmentioning
confidence: 99%
“…Management of diaphragmatic hernia is surgical and consists of reducing the viscera and sealing the diaphragmatic defect either by open thoracotomy or minimal access surgery. 18 The open approach allows not only diaphragmatic repair but also the management of potential complications, like perforation, strangulation and necrosis of the herniated organs. 5 In our case the defect was repaired by an open thoracotomy.…”
Section: Diaphragmatic Hernia Masquerading Hydropneumothoraxmentioning
confidence: 99%